LC-ESI-MS/MS Analysis of Secondary Metabolites of Different St. John's Wort (Hypericum perforatum) Extracts Used as Food Supplements and Evaluation of Developmental Toxicity on Zebrafish (Danio rerio) Embryos and Larvae - Atalara, Mehmet Nuri; Kokturk, Mine; Altindag, Fikret; Ozhan, Gunes; Ozen, Tevfik; Demirtas, Ibrahim; Gulcini, Llhami (Elsevier, 2023)
Hypericum perforatum (St. John's wort) belongs to the Hypericaceae family and is one of the best known Hypericum species worldwide. It is a very popular and valuable medicinal plant widely distributed in Anato-lia. Hypericum perforatum contains many bioactive components that play a role in activities has been used as a food supplement. The extracts are used within safe dose range that are harmless and effective for health. When the SJW1, SJW2 and SJW3 fractions of St. John's Wort extracts were exposed to zebrafish embryos and larvae at different concentrations (5, 10, 100, and 300 mg/mL), the survival rates at 96th hour were deter-mined as 83.3, 27.5 and 2.5%, respectively. No significant changes were found in the malformation rates, and the larval emergence was found to be above 80% at 96th hour for all extracts. No caspase-3 expression was found at the 96th hour in the larvae. Similar secondary components of extracts were observed except quanti-tative differences. The use of samples in doses of 10 mg/mL and below as food supplement may be harmless, however, threshold dose values of H. perforatum extracts lower toxic doses may be due to the different amounts of secondary metabolites.& COPY; 2023 Published by Elsevier B.V. on behalf of SAAB.
Gulcin, Ilhami/0000-0001-5993-1668; Ozhan, Gunes/0000-0002-4806-5917; Atalar, Mehmet Nuri/0000-0003-2993-2605
Keywords: Hypericum Perforatum; Zebrafish; Survival Rate; Cytotoxicity; Phenolic Content